Mekanisme Keuangan dalam Struktur Modal Perusahaan - Mudawam, Safaul (UIN Sunan Kalijaga, 2008)
There are several Islamic modes of financing whichserve as alternatives to interest based financing. There is,however, divergence of views between theory and practiceabout the order of preference of these modes of financing. Thetheoreticians are, generally, of the view that profit-loss sharingshould be the most widely prevailing mode of financing in thefinancial system of Islam. Some theoreticians have been quitecritical of this practice. Profit-loss sharing techniques make thecapital owner share the profit according to-actually realizedproductivity. Thus, the actually realized return on profit is theprice of capital which will determine its allocation. Among PLStechniques, musyarakah may have an edge over mudarabah inthe sense that in musyarakah, capital owner has a right tointerfere in the management and hence can have some controlover the problems created by informational asymmetry andmoral hazards, mudarabah is void of any such control. Thisdivergence is a result of the fact that the capital user does nothave to bear the uncertainties that the capital owner does. Itmay also be noted that since an upper limit on their profit isfixed by the rent or the mark up which are not related to theprofitability of the enterprise, these techniques may not have asprimary a role in investment decision making as profit-losssharing techniques.